2014
DOI: 10.15386/cjmed-387
|View full text |Cite
|
Sign up to set email alerts
|

The study of oral liquid microcrystallization in children with gastro-esophageal reflux disease

Abstract: Background and aim.Patients with disabilities have a higher prevalence of caries and dental erosions than general population. This particularity may be assessed by the study of microcrystallization of saliva. We investigated the oral liquid microcrystallization in children with gastroesophageal reflux disease (GERD), a condition associated with dental erosions.Material and methods.54 children have been clinically examined: 27 children suffering from GERD with ages between 13 and 15, were included in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
4
0
5
Order By: Relevance
“…Other studies showed that patients having dental erosions presented separated crystals in the form of a branch or stem, placed relatively evenly over the whole surface of the dried droplet or a large amount of separated stellate crystals of an oval and irregular shape located isometrically. 35 The major components of the varnish that we tested were casein phosphopeptide, calcium phosphate, amorphous calcium phosphate and fluoride. They can contribute to increase the remineralising potential of saliva and to arrest the erosive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that patients having dental erosions presented separated crystals in the form of a branch or stem, placed relatively evenly over the whole surface of the dried droplet or a large amount of separated stellate crystals of an oval and irregular shape located isometrically. 35 The major components of the varnish that we tested were casein phosphopeptide, calcium phosphate, amorphous calcium phosphate and fluoride. They can contribute to increase the remineralising potential of saliva and to arrest the erosive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Also, lower buffering capacity, salivary flow rate, and pH were found in the GERD group compared to healthy controls [11]. Spinei et al [12] reported that the degree of micro-crystallization of saliva was substantially decreased and lower in children suffering from GERD when compared with healthy control group. The researchers stated that examination of the structural properties of a dried oral liquid drop in children with reflux disease revealed the markers of changes in the oral cavity.…”
Section: Diseases Of the Upper Digestive Tractmentioning
confidence: 95%
“…Some authors believe that this is due to the physicochemical characteristics of saliva (amount of protein, viscosity, pH) [8,13]. According to many studies, the very phenomenon of facies formation, as well as the diversity of its structure, is based on complex molecular and physical mechanisms [14][15][16]. The increase in the number of protein components and the decrease in the viscosity of the oral fluid causes a violation of the structure of the crystals, thickening of the main trunks and processes, as well as the formation of many irregular crystallization centers or their complete absence.…”
Section: Figure 2 Crystallographic Patterns Of Oral Fluid Depending mentioning
confidence: 99%